CLANDESTINE MALAYSIAN WORKERS IN JAPAN - Abdul Aziz, Abdul Rashid (Penerbit USM, 2001)
Malaysia has played host to foreign workers from near and far over the last two decades, and neighbouring high wage countries, in turn, have played the same role to job-seeking Malaysians